Generation Existential : Heidegger's Philosophy in France, 1927-1961 - Kleinberg, Ethan (Book collections on Project MUSE., 2018)
When we think of Heidegger's influence in France, we tend to focus on such contemporary thinkers as Jacques Derrida, Michel Foucault, and Jean-François Lyotard. In Generation Existential, Ethan Kleinberg shifts the focus to the initial reception of Heidegger's philosophy in France by those who first encountered it. Kleinberg explains the appeal of Heidegger's philosophy to French thinkers, as well as the ways they incorporated and expanded on it in their own work through the interwar, Second World War, and early postwar periods. In so doing, Kleinberg offers new insights into intellectual figures whose influence on modern French philosophy has been enormous, including some whose thought remains under-explored outside France.Among Kleinberg's "generation existential" are Jean Beaufret, the only member of the group whom one could characterize as "a Heideggerian"; Maurice Blanchot; Alexandre Kojeve; Emmanuel Levinas; and Jean-Paul Sartre. In showing how each of these figures engaged with Heidegger, Kleinberg helps us to understand how the philosophy of this right-wing thinker had such a profound influence on intellectuals of the left. Furthermore, Kleinberg maintains that our view of Heidegger's influence on contemporary thought is contingent on our comprehension of the ways in which his philosophy was initially understood, translated, and incorporated into the French philosophical canon by this earlier generation.